Islamic Moderation Through Education Characters of Aswaja An-Nahdliyyah - Ahmad Saefudin; Al Fatihah Al Fatihah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
This study aims to elaborate the strengthening of Islamic moderateism through Aswaja An-Nahdliyyah character education. The researcher describes the behavior of Aswaja An-Nahdliyyah character education practiced by Islamic educational institutions as a basis for strengthening religious moderatism. The role of Islamic education institutions in applying moderate Islamic understanding in this disruption era is necessary. Because, students are faced with conditions of changing the order of values ​​and traditions that are very fast and unexpected. Through a descriptive-qualitative approach, data collection is done by interview, observation, and documentation. Through the frame of character education theory, the data analyzed using the stages of reduction, presentation, and drawing conclusions. Apparently, Aswaja An-Nahdliyyah's character education at MTs. Miftahul Huda Bulungan Pakis Aji Jepara was developed through teaching the value of tawassuth, tawazun, tasamuh and i'tidal. The implementation as culture of madrasa, such as the obligation to pray before starting the lesson, orderly running pickets, praying dzuhur in congregation, wearing school uniforms, preserving ancestral culture, familiarizing greetings, sympathetic care routinely for yatama and dhuafa, maintaining the cleanliness of the madrasa environment, and a ban on littering the classroom walls. The limitation of this study has specific scope. That is the focus on strengthening religious moderateism in Islamic educational institutions which are under the shelter of the LP. Maarif NU Jepara Regency. There are still gaps for other researchers to conduct development research outside of that scope.